Aktivitas Antibakteri dan Antioksidan Kain Tenun Timor Setelah Mordanting dengan Biomordan Tanin Kulit Biji Asam - Eka Maria Sanit; Risna Erni Yati Adu; Maria Magdalena Kolo; Elisabeth Korbafo (Saintek Lahan Kering, 2023)
The use of natural dyes in the textile industry, especially in dyeing Timorese woven fabrics, is increasingly in demand, however, the resulting colors tend not to fade easily against washing, so mordant is needed as a binder for colors and fabric fibers. Dyes and mordant derived from natural materials, apart from functioning as coloring agent and color enhancer, also have functional activities such as antibacterial and antioxidant. This study was conducted to examine the antioxidant and antibacterial activity of Timorese weaving using curcumin and biomordan tannin dyes against the growth of Escherichia Coli and Staphylococcus Aureus bacteria. Prior to the antioxidant activity test using the DPPH method and the antibacterial test using the difussion method, a mordanting process was carried out with variations of mordant and coloring of woven fabrics. The results of the inhibition zone measurements showed that woven fabrics dyed without the application of biomordan tannins had strong antibacterial activity with an inhibition zone diameter of 2.0 mm. Meanwhile, the highest antioxidant activity was found in fabrics colored with curcumin and fixed with biomordan, which was 58.11 ppm.